2017
DOI: 10.1108/ijppm-09-2016-0193
|View full text |Cite
|
Sign up to set email alerts
|

Digitalization of learning resources in a HEI – a lean management perspective

Abstract: Purpose Lean is considered as a major management approach for improving operational productivity and organizational performance. It is a systemic philosophy that emphasizes on fulfilling customer needs, waste minimization, and a commitment to a culture of continual improvement. In recent years, many higher education institutions (HEIs) have leveraged on the use of technology to provide flexibility in learning and just-in-time training for learners in the efforts to improve both the internal processes of course… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(41 citation statements)
references
References 27 publications
0
37
0
4
Order By: Relevance
“…Brown (2013) and Shieladevi and Rahman (2016) take a change management perspective. Other theories taken from the management field include learning organisations (Trevitt et al, 2017) and lean management (Tay & Low, 2017).…”
Section: Leadership Theoriesmentioning
confidence: 99%
See 2 more Smart Citations
“…Brown (2013) and Shieladevi and Rahman (2016) take a change management perspective. Other theories taken from the management field include learning organisations (Trevitt et al, 2017) and lean management (Tay & Low, 2017).…”
Section: Leadership Theoriesmentioning
confidence: 99%
“…Cluster 2 results studied leadership from the perspective of stakeholders who are not themselves in TEL leadership roles: change management from teachers' perspective (Sheiladevi & Rahman, 2016); teachers' perceptions of organisational culture (Zhu, 2015), related to a previous study involving both teachers and students (Zhu & Engels, 2014); futures visioning with deans and lecturers (Inayatullah & Milojevic, 2014); instructional designers and e-learning production staff (Ashbaugh, 2013;Tay & Low, 2017) students' perceptions of leadership in online instructors (Bogler, Caspi, & Roccas, 2013).…”
Section: Empirical Studies 2013-2017mentioning
confidence: 99%
See 1 more Smart Citation
“…The literature review covered the study of learning spaces, simulators, and games, among others; however, none of them showed significant evidence of educational possibilities where developed interactive methods and experiential learning spaces to design products and manufacturing processes. This review can also refer to focus on other aspects of education [27][28][29][30][31][32][33][34][35][36].…”
Section: Literature Reviewmentioning
confidence: 99%
“…There are similarities between the Lean Management philosophy and improvement strategies applied in organizations. Tay and Low (2017) report the case of a digital transformation in a Higher Education Institution, which evolved from the traditional printed materials to digital formats, simplifying its internal operations and creating value for the teaching and learning community. Wagner et al (2018), who propose a concept of integration to enhance Industrie 4.0 technologies in industrial value streams, using elements of design thinking.…”
Section: Lean Office Implementationmentioning
confidence: 99%